PELATIHAN CUCI KAKI DIABETES UNTUK PENCEGAHAN ULKUS KAKI LANSIA - Purwaningsih, Iswanti; Margaretha, Sumarti Endah Purnamaningsih Maria; Iswantiningsih, Elisabeth; Prihastuti, Mizan (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2025)
Diabetes mellitus is a chronic metabolic disease that increases the risk of foot complications in the elderly. This community service activity aimed to improve the knowledge, skills, and awareness of elderly individuals in performing proper diabetic foot care through education and foot washing practice. The program was conducted in Desa Mangir Lor, Sendangsari, Pajangan, Bantul, with four elderly diabetic participants. A descriptive-participatory approach was used, including initial observation, health education, and hands-on foot care practice. Results showed improvements in foot hygiene, nail care, and awareness of foot condition monitoring. Most participants followed the procedure well, although some steps required guidance. The impact was reflected in increased knowledge, skills, and awareness, with potential reduction in the risk of foot complications. In conclusion, structured and routine diabetic foot care training effectively prevents complications and enhances the quality of life of elderly diabetic patients.